Persistence and safety of anti-TNF biosimilars versus originators in immune-mediated inflammatory diseases: an observational study on the French National Health Data System - Mahmoud Zureik; Lea Hoisnard; Emilie Sbidian; Hugo Jourdain (RMD Open)
Objectives Biosimilar-originator equivalence has been demonstrated in phase 3 trials in a few indications of infliximab, etanercept and adalimumab. The objective of our study was to compare the persistence and safety of biosimilars versus originators in all the licensed indications of these molecules.Methods We used data from the French National Health Data System (SNDS), covering 99% of the French population, to identify infliximab, etanercept and adalimumab initiators from biosimilar launch (January 2015, May 2016 and October 2018, respectively) to 30 June 2021. Patients were then followed for 1 year. Treatment persistence (duration without treatment discontinuation or modification) and safety (including severe infections, all-cause hospitalisation and death) were compared between originator and biosimilar users by Cox regressions weighting the populations on the inverse probability of treatment. Analyses were performed by molecule, by disease and by biosimilar product.Results From January 2015 to June 2021, 86 776 patients were included in the study: 22 670, 24 442 and 39 664 patients had initiated infliximab, etanercept and adalimumab, respectively; 49 752 (53%) were biosimilar initiators. We did not find any risk of discontinuation (HRs were below or around 1, here all pathologies and products together: infliximab 0.88 (0.80–0.97), etanercept 0.85 (0.81–0.90) and adalimumab 0.96 (0.91–1.00)) or safety event (infection: infliximab 0.97 (0.78–1.21), etanercept 1.04 (0.81–1.33) and adalimumab 0.98 (0.83–1.16); hospitalisation: infliximab 1.08 (0.96–1.23), etanercept 0.99 (0.87–1.11) and adalimumab 0.91 (0.83–0.99)) associated with biosimilar versus originator use.Conclusions Our study shows reassuring results regarding the persistence and safety of biosimilar tumour necrosis factor-alpha inhibitors compared with originators in all licensed indications.